Effect of Composition and Morphology of Electrospun Polyacrylonitrile/Polyvinylpyrrolidone (PAN/PVP) Nanofibers on Adsorption of Methylene Blue and Congo Red Dyes - Istiara Hanifah; Alex Triputra Lumban Tobing; Hanna Ronauli Permata Simamora; Anisa Fitri; Agita Phasa (Green and Sustainable Materials Society, 2026)
Synthetic dyes such as methylene blue (MB) and Congo red (CR) are persistent water pollutants requiring efficient removal. This study examines the effect of composition and morphology on the adsorption performance of electrospun polyacrylonitrile/polyvinylpyrrolidone (PAN/PVP) nanofiber membranes. PAN/PVP fibers with different PAN loadings (0.7–1.0 g, total polymer mass 1.3 g) were fabricated by electrospinning and subjected to hot-water soaking at 80 °C followed by thermal treatment at 200 °C. SEM and FTIR confirmed continuous nanofibrous networks containing both PAN and partially removed PVP, with only subtle morphological differences among compositions. Batch adsorption tests showed preferential uptake of MB over CR, with the highest MB capacity of 8.38 mg g−1 obtained for the PAN/PVP-8 membrane and the highest CR capacity of 3.32 mg g−1 obtained for the PAN/PVP-10 membrane, with only modest variation among the other ratios. Kinetic analysis revealed that MB and CR adsorption follow a pseudo-second-order model, indicating surface-controlled uptake and suggesting that further improvement will require targeted surface functionalization.